Recurrence Relations and Hilbert Series of the Monoid Associated with Star Topology - Jiang-Hua Tang; Zaffar Iqbal; Abdul Rauf Nizami; Mobeen Munir; Faiza Azam; Jia-Bao Liu (Journal of Mathematics)
Affine monoids are the considered as natural discrete analogues of the finitely generated cones. The interconnection between these two objects has been an active area of research since last decade. Star network is one of the most common in computer network topologies. In this work, we study star topology Sn and associate a Coxeter structure of affine type on it. We find a recurrence relation and the Hilbert series of the associated right-angled monoid MSn∞. We observe that the growth rate of the monoid MSn∞ is unbounded.